The Diversity of Medicinal Plant Used by Local Community in Borneo, Indonesia: A Review - Nina Sari, Tri Astuti; Nurfitriani, Desty; Mutamimah, Rofiatul; Yudianto; Wakhidah, Anisatu Z (Tropical Biopharmaca Research Center, IPB University, 2025)
As one of the biggest islands in Indonesia, Borneo or Kalimantan, is considered one of the lungs of the world. The local communities utilize the large biodiversity in Borneo as traditional knowledge on medicinal use. The purpose of this article was to find out data on the diversity of medicinal plants utilized by local communities as well as the parts of plants used, the preparation in the use of medicinal plants, and the phytochemical content of several types of plant species that are most widely used in the Kalimantan region. This article was developed using the literature review method by searching for articles, journals and literature on Google Scholar. A total of 204 species from 74 families are utilized by the people of Kalimantan as medicine. The results showed that the types of plants that the people of Kalimantan widely use came from the Asteraceae family (16 species), Euphorbiaceae (15 species), Rubiaceae (11 species), Zingiberaceae (10 species), and others. The local people of Kalimantan mostly utilize plant leaves and roots by boiling since the boiling method is more effective in the healing process for fever and stomach pain. The people of Kalimantan most often apply medicinal plants by boiling them and then drinking them because this treatment is the most effective. It is believed that drinking it can accelerate healing. Therefore, there is a need for new knowledge and data collection related to the use of plants as medicine by the people of Kalimantan.